1986
DOI: 10.1126/science.3080804
|View full text |Cite
|
Sign up to set email alerts
|

Protein Modification by Amino Acid Addition Is Increased in Crushed Sciatic But Not Optic Nerves

Abstract: Rat optic and sciatic nerves were crushed, and 10 minutes to 3 days later nerve segments between the crushed site and the cell body were removed and assayed for posttranslational protein modification by amino acid addition. Protein modification was comparable in intact optic and sciatic nerves, but in sciatic nerves increased to 1.6 times control levels 10 minutes after crushing and reached a maximum of ten times control levels by 2 hours. In optic nerves activity was decreased throughout the time course studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…; Shyne‐Athwal et al . ; Chakraborty and Ingoglia ). Such differential effects of Arg incorporation into proteins following damage to nerves of the peripheral nervous system (PNS) versus central nervous system (CNS) suggest that triggering of post‐translational protein arginylation may be related to the greater plasticity often observed for PNS nerves in response to various types of injury.…”
Section: Nerve Regeneration and Protein Arginylationmentioning
confidence: 99%
See 1 more Smart Citation
“…; Shyne‐Athwal et al . ; Chakraborty and Ingoglia ). Such differential effects of Arg incorporation into proteins following damage to nerves of the peripheral nervous system (PNS) versus central nervous system (CNS) suggest that triggering of post‐translational protein arginylation may be related to the greater plasticity often observed for PNS nerves in response to various types of injury.…”
Section: Nerve Regeneration and Protein Arginylationmentioning
confidence: 99%
“…Low or absent ATE1 activity may be associated with the lack of regenerative capacity characteristic of mammalian CNS nerves (Shyne‐Athwal et al . ; Chakraborty and Ingoglia ). Regenerative responses in PNS nerves involve coordination of multiple separate processes (Gumy et al .…”
Section: Roles Of Ate1 In the Nervous System Beyond Protein Degradationmentioning
confidence: 99%
“…et al (1992) and Shyne-Athwal et al (1986) found that in vitro arginylated proteins obtained from damaged sciatic nerves are recognized by an antibody to ubiquitin and that the arginylation reaction is activated during nervous system regeneration. However, arginylation is not always the signal for the binding of ubiquitin.…”
Section: Introductionmentioning
confidence: 98%
“…This system operates, in part, as a mechanism whereby damaged proteins can be removed from the cytoplasm of a cell. We have found increases in posttranslational arginylation of proteins within 2 h of crush injury to sciatic nerves (Shyne-Athwal et al, 1988) and have speculated that these modifications are targeting damaged proteins for ubiquitin-mediated degradation (Shyne-Athwal et al, 1986, 1988Chakraborty et al, 1990b;Luo et al, 1990). Results of recent experiments support this speculation.…”
Section: Discussionmentioning
confidence: 81%